The optimization of graphene sensing layer against Escherichia coli - Muslihati, Atqiya (2021)
In the last decade, biosensor have been developed to detect E. coli. The system is complex with a receptor detecting specific target and producing a signal transducer to be a readout data. Previous E. coli sensors lacked selectivity, that potentially could detect other bacteria. In order to rectify this problem, this study aims to investigate the immobilization of anti–O and K E. coli antibodies on a SiO2/graphene film through the usage of a Pyrene butyric acid N–hydroxysuccinimide (PBANHS) linker. The investigation used some instruments like Raman spectroscopy, Atomic Force Microscopy (AFM), Field Effect Scanning Electron Microscopy (FE–SEM), and Current–Voltage (I–V) meter. In this research, the antibody was successfully immobilized on SiO2/graphene evidenced by the presence of pyrene (C–C) peak at <1000 cm–1 and (S–H) hybridization peak at 2506.25 cm–1 as PBANHS/anti–O and K E. coli antibody fingerprint in Raman spectra. Graphene height surface distribution increased 7.893 nm after PBANHS assembly and 0.364 nm after antibody immobilization. On the other hand, graphene maximum height decreased 0.46 nm after PBANHS assembly and 0.33 nm after antibody immobilization. Based on the electrical resistance, the sensing layer was able to detect E. coli against Staphylococcus aureus (S. aureus) with resistance difference 3.97 Ω and Limit of Detection (LOD) 16 CFU/mL. FE–SEM image shows the dispersion and attachment of E coli on the surface of the sensing layer, compared to the clustering of S. aureus. This new investigation lead to a new potential of specific immobilized anti–O and K E. coli antibodies on SiO2/graphene film as a selective sensing layer on E. coli sensor system.